THE EFFECTIVENESS OF THINK-PAIR-SHARE STRATEGY ON GRAMMAR SKILL OF SIMPLE PAST IN EIGHT GRADER STUDENTS JUNIOR HIGH SCHOOL OF RAUDLATUL ULUM GONDANGLEGI - Kholilur Rohman; Hanif Maulaniam Sholah (IAI Al-Qolam, 2022)
Effective strategy is very important to conduct by teacher in order to improve performance and quality of teaching and learning process. The investigation of using Think pair share technique to teach simple present tense has been conducted by some researchers. However, This research investigates teaching Simple Past using Think Pair Share Technique in eight grade of Junior High School of Raudlatul Ulum Gondanglegi. The aim is to know whether Think pair Share effects to the students score or not. This research uses a Quantitative Research, especially applies one group Pre-Experimental design. This research consists of pre-test and post-test for one group only. The effectiveness of the instructional treatment is measured by comparing average score of the pretest and the post test. The result found that based on the SPSS computation, the value of t- test is -793. It can be said that the null hypothesis is rejected. Then the significant difference found is 0,435 which means over than 0,05. So, the null hypothesis is rejected. Therefore, there is nothing difference between the students ability on before and after taught using TPS. So, it can be concluded that TPS is not effective yet in eight grader Junior High School students of Raudlatul Ulum Gondanglegi in writing skill especially for teaching Simple Past. Keyword: Strategy; Think-Pair-Share; grammar; simple past